2008
DOI: 10.1021/jp8026258
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Explanation of Nonexponential OH Decay in Reactions with Benzene and Toluene under Pseudo-First-Order Conditions

Abstract: OH radical reactions with benzene and toluene have been studied in the 200-600 K temperature range via the CBS-QB3 quantum chemistry method and conventional transition-state theory. Our study takes into account all possible hydrogen abstraction and OH-addition channels, including ipso addition. Reaction rates have been obtained under pseudo-first-order conditions, with aromatic concentrations in large excess compared to OH concentrations, which is the case in the reported experiments as well as in the atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 55 publications
2
58
1
4
Order By: Relevance
“…As indicated above, there have been a number of studies of both the H· abstraction and the OH· addition process of benzene, using fairly high levels of theory [24,25,27,29,46]. In addition to various specific levels of theory, the results differ also in whether or not zero-point vibrational terms have been added to the electronic energies.…”
Section: Benchmarksmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated above, there have been a number of studies of both the H· abstraction and the OH· addition process of benzene, using fairly high levels of theory [24,25,27,29,46]. In addition to various specific levels of theory, the results differ also in whether or not zero-point vibrational terms have been added to the electronic energies.…”
Section: Benchmarksmentioning
confidence: 99%
“…The exothermicity of the addition process falls in the range 12.6-19.4 kcal/mol, prior to ZPE correction, and 16.4-18.3 kcal after this correction. The outlier is a 2008 CBS-QB3 calculation [46] of 10.4 kcal/mol. The barrier for this addition process is clearly less than 5 kcal/mol, but there is significant variation within this range, even some suggesting no barrier at all.…”
Section: Benchmarksmentioning
confidence: 99%
“…In the atmosphere, due to their high potential to react with reactive species such as hydroxyl ( Å OH), nitrate radical (NO 3 ), and ozone (O 3 ), oxidation of aromatic compounds to form nonvolatile and semivolatile organic chemicals is the primary fate process in the atmosphere [11][12][13]. In daytime, the reaction of aromatic hydrocarbons with hydroxyl radicals is the major atmospheric loss process [14][15][16]. Several previous experimental [17][18][19] and theoretical [20][21][22][23][24][25][26] studies have unraveled the elementary reactions involved in aromatic oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that in the presence of OH radical the main reaction path is OH addition to the aromatic ring to form a xylene-OH adduct (consuming $90% of OH radicals) with Habstraction from one methyl group to form a methylbenzyl radical (consuming $10% of OH radicals) being the minor route [18,[31][32][33][34]. In addition, theoretical investigations have mainly focused on OH-addition to xylene and the fate of xylene-OH adducts and intermediates [15,26,31,[34][35][36], whereas the H-abstraction mechanism for p-xylene oxidation following the initial OH attack and subsequent products have only been studied experimentally [22,25,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Computational kinetics calculations (Uc et al 2008) were performed, using quantum chemistry data for these reactions under pseudo-first-order conditions, in order to explain the observed Arrhenius plots. We employed a theoretical approach that is in line with both experimental and environmental conditions and that takes into account the fact that aromatic concentrations are in large excess compared to OH concentrations.…”
Section: Competing Mechanismsmentioning
confidence: 99%